Vitamin D receptor gene polymorphism in Madura pregnant women with hypertension: a case control study - Setiarsih, Dini; Hastuti, Pramudji; Nurdiati, Detty Siti (2022)
Background: Genetic factors are important considerations in the etiology of preeclampsia and gestational hyper- tension. Several previous studies have shown an association of Vitamin D receptor (VDR) gene polymorphisms with hypertension in pregnancy. However, the number of studies is still very limited and the results differ from one another. Aim of the study: This study aimed to analyze the polymorphisms of rs2228570 and rs731236 of the VDR gene in subjects with hypertension and non-hypertension in pregnancy in Madura ethnicity. Subjects and methods: The researchers conducted tests for two polymorphisms in the VDR gene among 210 subjects consisting of 105 pregnant women with hypertension and 105 non-hypertension pregnant women from Madura ethnicity. The rs2228570 (T>C) and rs731236 (C>T) polymorphisms were detected by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism. All data were analyzed by T-tests and Chi-Square tests. Results: The TT genotype frequency of rs2228570 (15.2%) in the hypertension group was higher than in the control group (6.7%) (p = 0.047). Subjects with the TT genotype at rs2228570 showed a 3.048 times greater risk of developing hypertension than the CC genotype (OR = 3.048: 1.135–8.183, p = 0.023). The T allele frequency of rs2228570 (40.5%) in the hypertension group was higher than in the control group (30.5%) (p = 0.032). Subjects with the T allele had 1.551 times greater risk of developing hypertension. There was no significant difference in genotype and allele of rs731236 between hypertension subjects and controls. Conclusion: The TT genotype and T allele of rs2228570 in the hypertension group were risk factors for hyperten- sion in this study. While the TT genotype and T allele at rs731236 were not risk factors for hypertension in pregnancy. Genotyping of VDR gene polymorphisms in pregnant women is expected to be useful in strategies for treating hyper- tension in pregnancy.